1995
DOI: 10.1074/jbc.270.43.25968
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the blk Gene in Human B Lymphocytes Is Controlled by Two Promoters

Abstract: Genomic DNA containing the first exon and 5-flanking region of the human protein tyrosine kinase, blk, was isolated. Sequence analysis identified a TG repeat element in this region with enhancer activity, but no TATA or CCAAT sequences were found. Two blk transcripts of 2.2 and 2.5 kilobases were identified in various B-cell lines by Northern blot analyses, and primer extension experiments demonstrated two clusters of multiple transcription start sites. Subsequent promoter analyses by transient transfection as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 56 publications
0
16
0
1
Order By: Relevance
“…In these experiments potential Z-DNA-forming sequences have been either deleted from or introduced into reporter plasmids, and inhibitory or enhancing effects were observed (24)(25)(26). The contribution of the potential Z-DNA-forming sequences to the observed effects is probable, but adjacent sequences also may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments potential Z-DNA-forming sequences have been either deleted from or introduced into reporter plasmids, and inhibitory or enhancing effects were observed (24)(25)(26). The contribution of the potential Z-DNA-forming sequences to the observed effects is probable, but adjacent sequences also may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has previously been reported that Jurkat cells express low levels of Blk mRNA. 22,39 However, protein expression of Blk was not observed in the Jurkat cells ( Figure 1C). Confirming the identity of the band recognized as Blk, transfection of the malignant CTCL cell lines with Blkspecific siRNA induced a selective down-regulation of the band, whereas the expression of Erk remained unaffected ( Figure 1D; data not shown).…”
Section: Selective Expression Of Blk In Malignant Ctcl Cell Linesmentioning
confidence: 99%
“…39,41,42 CTCL cell lines expressed both of the NF-B subunits, p65 and p50, with the latter being overexpressed, compared with nonmalignant T-cell lines ( Figure S1). In contrast, no expression of Pax-5 mRNA was detected (data not shown), suggesting that NF-B is a candidate transcription factor in CTCL.…”
Section: Expression Of Blk Is Induced By Nf-bmentioning
confidence: 99%
“…3D and data not shown). We examined 10 downstream target genes (seven positively regulated direct target genes and three negatively regulated genes) of PAX5 (10)(11)(12) and found that four, including ATP1B1, BLK, NEDD5 and TCF7L2, were down-regulated by induction of either PAX5-C20orf112S or PAX5-C20orf112L protein. However, expression of other reported PAX5 downstream target genes, including three positively regulated direct target genes (IRF8, BST1, CD19) and three negatively regulated genes (CCR2, CCR5, NOTCH1) were not affected by the induction of expression of the fusion proteins in these cells.…”
Section: Genes Involved In Unbalanced Translocationsmentioning
confidence: 99%